Metropolis : Internationale Kunstausstellung Berlin 1991. - Bonito Oliva, Achille; Deitch, Jeffrey; Faust, Wolfgang Max; Flusser, Vilém; Groys, Boris; Joachimides, Christos M.; Kamper, Dietmar; Rosenthal, Norman; Tannert, Christoph; Virilio, Paul; Martin-Gropius-Bau, Berlin; Rizzoli, New York (Ostfildern-Ruit : Cantz Verlag, 1991)
Armleder, John M ; Artschwager, Richard ; Balka, Miroslaw ; Baranek, Frida ; Baselitz, Georg ; Bleckner, Ross ; Borofsky, Jonathan ; Bustamante, Jean-Marc ; Byars, James Lee ; Cabrita Reis, Pedro ; Cavenago, Umberto ; Clegg & Guttmann ; Daniels, René ; Davenport, Ian ; Dokoupil, Jiri Georg ; Eichhorn, Maria ; Fabre, Jan ; Fermariello, Sergio ; Finlay, Ian Hamilton ; Fischli & Weiss ; Förg, Gunther ; Fritsch, Katharina ; Gilbert & George ; Gober, Robert ; Görlich, Ulrich ; Görss, Rainer ; Guzman, Federico ; Halley, Peter ; Heisterkamp, Fritz ; Herold, Georg ; Hill, Gary ; Holzer, Jenny ; Iglesias, Cristina ; Kaufmann, Massimo ; Kelley, Mike ; Kenmochi, Kazuo ; Kessler, Jon ; Knoebel, Imi ; Koons, Jeff ; Kounellis, Jannis ; Kovacs, Attila ; Kuitca, Guillermo ; Lappas, George ; Laubert, Otis ; Merz, Gerhard ; Metzel, Olaf ; Morimura, Yasumasa ; Mucha, Reinhard ; Muñoz, Juan ; Nauman, Bruce ; Noland, Cady ; Odenbach, Marcel ; Oehlen, Albert ; Perrin, Philippe ; Prigov, Dmitry Alexandrovich ; Prince, Richard ; Richter, Gerhard ; Ruff, Thomas ; Ruscha, Edward ; Sarmento, Julião ; Schnabel, Julian ; Sherman, Cindy ; Starn, Doug & Mike ; Steinbach, Haim ; Trockel, Rosemarie ; Viola, Bill ; Wall, Jeff ; West, Franz ; Whiteread, Rachel ; Woodrow, Bill ; Wool, Christopher ; Zakharov, Vadim
2 ex. : duits + eng.
algemene bibliografie p. 330-335
biog. auteurs p. 336
biog., tent., bibliog. p. 270-320
Duits
Engels
Keywords: Berlin